Plagues, Politics, and Policy: A Chronicle of the Indian Health Service, 1955-2008 - DeJong, David H. (Lexington Books, 2010)
Plagues, Politics, and Policy is an overview of the major health challenges confronting American Indians and Alaska Natives over the past fifty years and is a case study of the federal government's attempt to provide medical services to a categorical group of people in the United States. While it is not a detailed analysis of what socialized healthcare should or should not look like, it does examine the major social and political issues affecting the delivery of health services to American Indians and Alaska Natives. This book addresses broad policy questions, such as whether or not American Indians and Alaska Natives have received better healthcare since the Indian medical service transferred from the Bureau of Indian Affairs to the Public Health Service in 1955. In the initial decades of Public Health Service control of IHS, the problems of infectious diseases were largely eliminated, but they have been replaced by new challenges which will require IHS and tribal leaders to work together to come up with solutions. Many American Indians and Alaska Natives also face public health challenges rooted in the social and political history of the federal Indian relationship. In this book, DeJong provides a path to improving the future of health care for American Indians and Alaska Natives.